From work to play: Exploring the preservation of the industrial building and its reactivation through adaptive reuse - Kraus, Barbara (My University, 2023)
Industrial heritage often presents a unique challenge within the heritage and conservation discourse as its significance has been somehow recognized only in the last 50 years and its value is still frequently being dismissed. The question is also how do we approach their preservation as these usually large-scale buildings were mainly made to accommodate machinery, not human beings? Heritage preservation in general does not have one size fits all solution. Even though many may argue there is a preferred approach, which can often be seen in institutionally protected “monuments”. It is typically to maintain the objects and do only the necessary, minimal interventions. This often makes them objects that cannot be interacted with but that we passively view while listening to their story that was curated by someone else providing a set narrative. Industrial heritage can here provide more interesting opportunities for how to approach the preservation of a building. These were once places of work that people interacted with daily, and some may still remember them being in use. They were never intended as untouchable monuments but as functional buildings, always meant to change depending on the current needs. So, their new evolution and the idea of their change, even if just subtle, may feel like a more organic part of their life. Using the M-verkstaden in Gamlestaden, a former machine repair workshop for the SKF, built in the early 1900s, and situated in the heart of SKF’s complex, as a site of investigation, this thesis aims to look at the industrial heritage as valuable evidence of its time that can be used to inform and shape its new future. Documentation and mapping of the building play an important role in understanding the building and are used to influence the interventions. Interpreting stories of the past not as one set truth but as unfinished narratives forming a new public space that reactivates the area and allows people to connect and experience it in their own way.
Keywords: Industrial heritage; Preservation; Adaptive reuse; Public space